The Influence of Digital Marketing, Service Quality and Product Variety on Customer Loyalty of Kopi Daeng Cafe in Balikpapan (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to determine and analyse the influence of digital marketing, service quality and product variety partially on customer loyalty of Kopi Daeng Gunung Bakaran Balikpapan Branch. This study uses a quantitative approach with a survey method. The sampling technique in this study is Non- Probability Sampling with Incidental Sampling technique. Based on this technique, the number of samples in this study was 180 respondents who that be customers. The Data collection was carried out by distributing online questionnaires via Google Form to respondents who had made the purchasing at this place. The data analysis technique in this study used validity test, reliability test, classical assumption test, t test, f test, linear regression test and coefficient of determination test using the Statistical Package for the Social Sciences (SPSS) version 15.0 program. The results showed of the digital marketing variable did not have a significant effect on customer loyalty, the service quality variable did not have a significant effect on customer loyalty, while the product variety variable had a positive and significant effect on customer loyalty.